Diagnosis, clinical management, and emerging strategies for coronary artery disease in patients with cancer - Nicole Charbel; Karl Aramouni; Sam Sater; Firas Kreidieh (American Heart Journal Plus, 2025)
The intersection of cancer and coronary artery disease (CAD) presents complex clinical challenges requiring a multidisciplinary approach. Building on the first part of this review, which addressed epidemiology, shared risk factors, and pathophysiological mechanisms, this second part focuses on the diagnosis, screening, and management of CAD in patients with cancer, as well as management of cancer in CAD patients. Early identification of CAD remains challenging due to overlapping symptoms; thus, cardiovascular imaging modalities such as echocardiography, coronary computed tomography angiography, and cardiac magnetic resonance imaging, alongside cardiac biomarkers, are essential for accurate detection and risk stratification.Screening strategies emphasize baseline cardiovascular risk evaluation and long-term surveillance, particularly for cancer survivors exposed to cardiotoxic therapies. Management of CAD in this population requires individualized pharmacologic and interventional strategies, balancing thrombotic, bleeding, and oncologic risks. The use of percutaneous coronary intervention and coronary artery bypass grafting (CABG) must be tailored to patient-specific cancer prognosis and cardiovascular status.Moreover, several cancer therapies, including ERBB-2-targeted agents, angiogenesis inhibitors, and immune checkpoint inhibitors, are associated with cardiovascular toxicities, necessitating vigilant monitoring and timely interventions. Emerging fields such as anti-inflammatory therapy, clonal hematopoiesis of indeterminate potential integration, and artificial intelligence–based risk prediction offer promising strategies for improving outcomes. This second part of the review highlights the importance of a multidisciplinary cardio-oncology approach to optimize care for patients facing the dual burden of cancer and CAD.